2004
DOI: 10.1136/jmg.2004.018275
|View full text |Cite
|
Sign up to set email alerts
|

Germline E-cadherin mutations in hereditary diffuse gastric cancer: assessment of 42 new families and review of genetic screening criteria

Abstract: Background: Mutations in the E-cadherin (CDH1) gene are a well documented cause of hereditary diffuse gastric cancer (HDGC). Development of evidence based guidelines for CDH1 screening for HDGC have been complicated by its rarity, variable penetrance, and lack of founder mutations. Methods: Forty three new gastric cancer (GC) families were ascertained from multiple sources. In 42 of these families at least one gastric cancer was pathologically confirmed to be a diffuse gastric cancer (DGC); the other family ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
254
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(272 citation statements)
references
References 46 publications
11
254
0
1
Order By: Relevance
“…Genetic alterations, as LOH, which seem to be acquired later in HDGC progression, could be then targeted with drugs such as EGFR and ␣5-␤1-integrinblocking antibodies or transforming growth factor-␤-R small synthetic molecules to prevent cells from migrating and metastasis from establishing. [35][36][37][38][39][40] In conclusion, our data support the previously published rate of CDH1 promoter hypermethylation as a 2nd-hit in HDGC primary tumors, and adds LOH as a key mechanism, mainly in metastatic lesions. Because of the concomitance and heterogeneity of these alterations in neoplastic lesions and the plasticity of hypermethylated promoters during tumor initiation and progression, drugs targeting only epigenetic alterations might not be effective, particularly in patients with metastatic HDGC.…”
Section: Discussionsupporting
confidence: 91%
“…Genetic alterations, as LOH, which seem to be acquired later in HDGC progression, could be then targeted with drugs such as EGFR and ␣5-␤1-integrinblocking antibodies or transforming growth factor-␤-R small synthetic molecules to prevent cells from migrating and metastasis from establishing. [35][36][37][38][39][40] In conclusion, our data support the previously published rate of CDH1 promoter hypermethylation as a 2nd-hit in HDGC primary tumors, and adds LOH as a key mechanism, mainly in metastatic lesions. Because of the concomitance and heterogeneity of these alterations in neoplastic lesions and the plasticity of hypermethylated promoters during tumor initiation and progression, drugs targeting only epigenetic alterations might not be effective, particularly in patients with metastatic HDGC.…”
Section: Discussionsupporting
confidence: 91%
“…14 Using functional in vitro assays, we demonstrated that cells expressing pathogenic CDH1 missense mutations fail to aggregate and become more invasive, in comparison with cells expressing wild-type (WT) E-cadherin, 5,12,[15][16][17][18][19][20][21][22] supporting their pathogenic relevance.…”
Section: Introductionmentioning
confidence: 83%
“…5,12,[15][16][17][18][19]21 The slow aggregation assay showed that all the mutants have an impact on the cell-cell adhesion ability but the type of aggregation showed distinct phenotypes (Figure 7a). Comparing with the compact aggregates formed by the WT E-cadherin-expressing cells, some mutants display smaller cellular aggregates, such as mutants T340A, A634V, R749W, P799R and V832M, and others exhibited a close-to-isolated phenotype, as observed for mutants E757K and E781D, very similar to the phenotype of Mock cells.…”
Section: Cdh1 Missense Mutations Affect E-cadherin Subcellular Localimentioning
confidence: 99%
See 1 more Smart Citation
“…All PCR primers incorporated M13 forward or reverse sequencing tags to allow efficient sequencing of the PCR products. PCR, sequencing and sequence analysis were carried out as described previously, 32 with the exception that we used Big Dye Terminator Mix v3.1 (Applied Biosystems, Foster City, CA, USA) at 0.33 ml of mix per reaction in a total volume of 4 ml with 50 cycles amplification. Haploview 33 was used to calculate and display inter-SNP linkage disequilibrium (LD) information derived from sequence data.…”
Section: Study Subjectsmentioning
confidence: 99%